Habit transformation - Walter, Josephine Elizabeth (My University, 1907)
Introduction: Every young hereon should strive to make the body in which his habits are reserved, his friend and not his enemy. Every day our nervous tissue is storing up the result of our actions, and we know not what time the habit will grasp us with its firm grip which we cannot loosen, but if one at once gets under the sway of a habit, and wishes to escape from it, he must begin at once with all the determination he can possess, and not put it off until some more convenient time. Unless the result is apt to be disastrous, stop wholly, do not taper off. Give yourselves surroundings that will offer the least temptations, and put a good habit in its place whenever possible.
Citation: Walter, Josephine Elizabeth. Habit transformation. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Habits; Improving Habits; Good Behavior; Theses; Manuscripts (documents)